Path to discontinuance of pervasive mobile games: the case of Pokémon Go in Australia. Issue 2 (1st June 2020) - Butcher, Luke; Tucker, Oliver; Young, Joshua
Abstract : Purpose: Pervasive mobile games (PMG) expand the game context into the real world, spatially, temporally and socially. The most prominent example to date is Pokémon Go (PGo), which in the first 12 months of its launch achieved over 800 million downloads and huge revenues for Pokémon, its majority owner Nintendo, and its developer Niantic. Like many mobile apps and innovative services, PGo's revenue structure requires continual usage (through in-app purchases and sponsorships) as it is free to download. Thus, as many players discontinued after initial adoption, substantial drops in Nintendo's share price occurred alongside the damage to brand equity. Such a case highlights the need to extend scholarship beyond traditional 'adoption' and begin to truly illustrate and explain the consumer behaviour phenomenon of 'discontinuance', particularly in the emerging and lucrative domain of PMGs. Design/methodology/approach: Like many emerging marketing channels before it, large-scale discontinuance of PGo occurred and still remains unexplained in the academic literature. Herein, we address this shortcoming through a consumer case study methodology analysing a variety of data sources pertaining to PGo in Australia. Findings: The development of the P2D_PMG model provides a new conceptual framework to illustrate the distinct forms discontinuance manifests in, for the first time. Scholarly rigour of the P2D_PMGs is achieved through validating and extending Soliman and Rinta-Kahila's (2020) framework for 'discontinuance' through its five forms. These forms are revealed as access and on-boarding (rejection), disconfirmation and hedonic adaptation (regressive discontinuance), technological, social, third parties, and personal issues (quitting), re-occurrences of hedonic adaptation (temporary), and alternatives and iterations (replacement). Originality/value: Conceptual contributions are made in developing a model to explain what drives PMG discontinuance and when it occurs. This is particularly crucial for products with revenue structures built on continual usage, instead of initial adoption. In deriving data from actual players and aggregate user behaviour over an extended time period, the innovative case study methodology validates new discontinuance research in a manner other methods cannot. Managerial implications highlight the importance of CX, alpha/beta testing, promotion and research, gameplay design and collaboration/community engagement.